Thrombus aspiration in non-ST-elevation myocardial infarction – 12-month clinical outcome of the randomised TATORT-NSTEMI trial. Issue 1 (February 2017) - Meyer-Saraei, Roza; de Waha, Suzanne; Eitel, Ingo; Desch, Steffen; Scheller, Bruno; Böhm, Michael; Lauer, Bernward; Gawaz, Meinrad; Geisler, Tobias; Gunkel, Oliver; Bruch, Leonhard; Klein, Norbert; et al.
Background: In the randomised TATORT-NSTEMI trial routine thrombus aspiration in comparison with standard percutaneous coronary intervention (PCI) did not reduce the primary endpoint of microvascular obstruction assessed by cardiac magnetic resonance imaging in patients with non-ST-elevation myocardial infarction (NSTEMI). So far, no data on long-term outcome of head-to-head comparisons between both treatment strategies in NSTEMI patients have been reported. Methods: The prospective, controlled, multicentre, randomised, open-label TATORT-NSTEMI trial assigned patients with NSTEMI and thrombus-containing lesions to aspiration thrombectomy plus PCI ( n =221) or standard PCI only ( n =219). The primary endpoint of the current analysis was the occurrence of major adverse cardiac events defined as the composite of death, myocardial reinfarction, target vessel revascularisation, and new congestive heart failure at 12-month follow-up. In addition, functional outcome and quality of life were assessed. Results: At one year, major adverse cardiac events occurred in 19 patients in the thrombectomy arm and 29 patients in the standard PCI group (8.7% vs . 13.4%, relative risk 0.63, 95% confidence interval 0.35–1.12, p =0.11). The individual components of the combined endpoint such as death ( p =0.20), myocardial reinfarction ( p =0.73), target vessel revascularisation ( p =0.42), and congestive heart failure ( p =0.18) were similar in both groups. Functional outcome and quality of life did not differ significantly between both groups (Canadian Cardiovascular Society class: p =0.68, New York Heart Association class: p =0.70 and EuroQol5D score: p=0.96). Post-hoc analyses revealed consistent results with regard to the occurrence of major adverse cardiac events across a wide range of subgroups (all p >0.05). Conclusions: In this first randomised trial on thrombectomy in NSTEMI patients, routine thrombus aspiration before PCI did not improve clinical outcome at 12-month follow-up.